FAKTOR- FAKTOR YANG MEMPENGARUHI STRES MAHASISWA PROGRAM TRANSFER KEPERAWATAN YANG SEDANG MENYUSUN SKRIPSI - Agnes Putri S Marbun; Arneliwati Arneliwati; Yufitriana Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Stress is a physical and psychic reaction in the form of uncomfortablefeeling, or depressed to a pressure or demandsbeing faced. One of the demands faced by final-year students is the process of 'research writing. It results in manystudents experience stress while compiling the research. This study aimed to determine the factors that affect the stressof nursing program transfer students who are preparing the research. This research used descriptive correlationaldesign with cross-sectional approach. The sample was 73 respondents taken by total sampling technique. The resultsshowed that 4.1% of respondents experienced mild stress, 91.8% of respondents experienced moderate stress and 4.1%of respondents experienced severe stress. The result of the research also pointed that there was an influence ofbehaviortowards students’ stress (p-value = 0,028), there was a cognitive influence to student stress (p-value = 0,049),there wasan emotional influence to students’ stress(p-value = 0,038), there was an influence of physical environmentto students’ stress(p-value = 0,026) whereas physical condition did not affect the students’ stress (p-value = 0,158)and socio-cultural environment also did not affect thestudents’ stress(p-value 0.794). It is expected that students who are in writing a research to prepare themselves physically and psychologically to face research so that it can prevent or minimize the stress due tothe research.Keywords: factors, nursing, research, stres, student